CONTRIBUTION A L’ETUDE DES CARACTERES MORPHO BIOMETRIQUES DES PETITS RUMINANTS AU NIVEAU DE LA REGION DE SOUK AHRAS - Chahinez,KOURARI (My University, 2024)
Our study was carried out in the wilaya of Souk Ahras, on 14 private farms rearing small ruminants (goats and/or ewes), spread over 07 communes: OuledDriss, Mrahna, Dekma, Taoura, Ainsinour (El Meriss), El khdara, Tifach, and Souk Ahras (Ville Fibeaur) during the period from the beginning of March to the end of May 2024, with the aim of studying andcharacterising the morpho-biometric traits of small ruminants, including 30 morphological, quantitative and qualitative traits on a sample of 43 sheep and 49 goats. The results of the field survey showed that: the majority of farmers in the study region are men (92.86℅) aged over 40 (64.29%); their flocks are usually mixed (sheep and goats): 57.16%. The sheep in the study area had a 100% white fleece with a predominantly white head (88.38%) compared with 11.62% of brown heads, and mean values (cm) for HG, HS, LC, TP and LSL for adult males and females respectively: 80. 14±7.02 vs 77.50±4.69 ; 81.82±6.51 vs77.96±4.82 ; 87.89±7.68 vs 84.53±10.40 ; 124.89±15.48 vs 98.85±9.37 ; 80.07±8.27 vs 72.10±9.50. As for the goats in the population studied, they showed a wide range of head colours, with high rates of horn presence (80%) compared with 20% that were clodded and had goatees in 51.09% of cases. And they also showed mean values for HG, HS, LC, TP, LSL in the order of: 78.23±9.17 vs 73±4.59; 79.96±8.87 vs 75±3.90; 77.8±9.18 vs 75.27±7.49; 91.79±8.81 vs 85.29±9.17; 71±8.41 vs 68.61±6.97 in adult males and females respectively. تمت دراستنا في ولاية سوق أهراس، في 14 مزرعة خاصة لتربية الحيوانات الصغيرة (الماعز و/أو الأغنام)، المنتشرة عبر 07 بلديات: أولاد دريس، المراهنة، دكمة، التاورة، عين سينور (المريس)، الخضراء، تيفاش، وسوق أهراس (فيبور)، وذلك خلال الفترة من بداية مارس إلى نهاية مايو 2024. الهدف من الدراسة هو دراسة وتوصيف الصفات المورفوبيومترية للحيوانات الصغيرة، وتشمل 30 سمة مورفولوجية كمية ونوعية على عينة تتكون من 43 رأسا من الأغنام و49 رأسا من الماعز. أظهرت نتائج الدراسة الميدانية أن مربي الحيوانات في منطقة الدراسة هم في الغالب رجال (92.86٪) يتجاوز عمرهم الأربعين عامًا (64.29٪)، وأن لديهم مزارع غالباً ما تكون مختلطة بين الأغنام والماعز بنسبة 57.16٪. أما بالنسبة للأغنام في المنطقة المدروسة، فقد أظهرت أن لديها صوف أبيض بنسبة 100٪ مع رؤوس بيضاء بنسبة 88.38٪ مقابل 11.62٪ للرؤوس البنية، وأظهرت قيم متوسطة (بالسنتيمتر) للمواصفات HG، HS، LC، TP، LSL عند الذكور والإناث البالغين على التوالي: 80.14±7.02 مقابل 77.50±4.69؛ 81.82±6.51 مقابل 77.96±4.82؛ 87.89±7.68 مقابل 84.53±10.40؛ 124.89±15.48 مقابل 98.85±9.37؛ 80.07±8.27 مقابل 72.10±9.50. أما بالنسبة للماعز في السكان المدروسين، فقد أظهرت تنوعًا في ألوان الرؤوس، مع وجود نسب عالية من القرون (80٪) مقابل 20٪ لأولئك الذين لا يمتلكون قرون ويحملون لحى في 51.09٪ من الحالات وأظهرت الدراسة أيضًا قيم متوسطة للمواصفات HG، HS، LC، TP، LSL للماعز، وهي كالتالي للذكور والإناث البالغين على التوالي: 78.23±9.17 مقابل 73±4.59؛ 79.96±8.87 مقابل 75±3.90؛ 77.8±9.18 مقابل 75.27±7.49؛ 91.79±8.81 مقابل 85.29±9.17؛ 71±8.41 مقابل 68.61±6.97. Notre étude a été réalisée au niveau de la wilaya de Souk Ahras , au niveau de 14 exploitations privées élevage de petits ruminants (chévres et /ou brebis) , réparties sur 07 communes : Ouled Driss, Mrahna, Dekma, Taoura ,Ain sinour (El Meriss) , El khdara, Tifach, et Souk Ahras (Ville Fibeaur) et cela pendant la période qui s’étale entre début Mars et fin Mai 2024, dans l'objectif d’étude et de caractériser les traits morpho-biométriques des petits ruminants, comprenant 30 caractères morphologiques, quantitatifs et qualitatifs sur un échantillon formé de 43 têtes ovines et 49 têtes caprines. Les résultats obtenus de l’enquête du terrain, ont montré que : les éleveurs de la région d’étude sont majoritairement des hommes (92.86℅) âgés de plus de 40 ans (64.29 % ) ; disposent des troupeaux le plus souvent mixtes (ovins et caprins) : 57.16%. Les ovins de la région d’étude, ont montrés une toison 100% blanche avec une tête majoritairement blanche (88.38%) vs 11.62 % de tête brune, et des valeurs moyenne (cm) concernant l’HG, l’HS, LC, TP, LSL qui sont respectivement chez les mâles et les femelles adultes : 80.14±7.02 vs 77.50±4.69 ; 81.82±6.51 vs77.96±4.82 ; 87.89±7.68 vs 84.53±10.40 ; 124.89±15.48 vs 98.85±9.37 ; 80.07±8.27 vs 72.10±9.50. Quant aux caprins de la population étudiée, ils ont montré de panachure de couleurs de tête, avec des taux élevés de présence de cornes (80 %) vs 20% qui sont mottes et portent des barbiches dans 51.09% des cas. Et ils ont également montré des valeurs moyennes de l’HG, HS, LC, TP, LSL de l’ordre : 78.23±9.17 vs 73±4.59 ; 79.96±8.87 vs 75±3.90 ; 77.8±9.18 vs 75.27±7.49 ; 91.79±8.81 vs 85.29±9.17 ; 71±8.41 vs 68.61±6.97 chez les mâles et les femelles adultes respectivement.
Keywords: Sheep; goats; morpho-biometric characterisation; breeding; Souk Ahras. ...; أغنام، ماعز، توصيف مورفوبيومتري، تربية، سوق أهراس...; Ovins; caprins; Caractérisation morpho-biométrique; élevage; Souk Ahras.